Submental method for orotracheal intubation in treating facial trauma - Manganello-Souza, Luiz Carlos (1998)
OBJECTIVE: To demonstrate an alternative method for intubating patients with fractures of maxilla and nose, prior to surgery. DESIGN: Cases Report. PARTICIPANTS: We studied 10 patients with facial fractures that affected maxilla and nose. INTERVENTION: The patients were submitted to surgery under general anesthesia and submental oro-tracheal intubation. RESULTS: This type of intubation allowed the surgical team to work on the whole face of the patient and left no visible scar. CONCLUSION: This procedure is indicated for patients with fractures of maxilla and nose who need surgical intervention under general anesthesia.